Amorphous-Carbon-Supported Ultrasmall TiB2 Nanoparticles With High Catalytic Activity for Reversible Hydrogen Storage in NaAlH4 - Zhang, Xin; Zhang, Xuelian; Ren, Zhuanghe; Hu, Jianjiang; Gao, Mingxia; Pan, Hongge; Liu, Yongfeng (Frontiers in Chemistry, 2020)
Here, we report amorphous carbon-supported 2-3 nm-sized TiB2 nanoparticles as highly active catalyst for hydrogen storage in NaAlH4. Nano-TiB2@C was synthesized by a facile calcination process at 550 °C with Cp2TiCl2 and MgB2 (molar ratio, 1:1) as precursors. The addition of 7 wt% nano-TiB2@C reduces the onset dehydrogenation temperature of NaAlH4 by 100 °C to 75 °C, and delivers a practically available hydrogen capacity of 5.04 wt%. The 7 wt% nano-TiB2@C-containing NaAlH4 sample releases 5.04 wt% of H2 at 140 °C within 60 min, and is completely hydrogenated at 100 °C within 25 min under 100 bar of hydrogen. More importantly, hydrogen capacity remained almost unchanged after 20 cycles, representing a stable cyclability, which is greatly better than those catalyzed by Ti halides or TiO2. The highly stable catalytic function is closely related to the in situ formed Ti-Al intermetallics, which greatly facilitates the dissociation and recombination of H-H and Al-H bonding.